Bibliometric analysis of published literature on taxation in Malaysia, based on Scopus database - Ya’u, Abba; Saad, Natrah (Institute for Management and Business Research (IMBRe), Universiti Utara Malaysia, 2021)
Taxation research has received considerable attention from many scholars, practitioners and policymakers across the globe. Many scholars have also conducted research on taxation in the Malaysian context. However, papers that track the trends of such research are scanty in the existing literature. The aim of this study is to review the trend and frequencies of published literature on taxation in Malaysia based on the Scopus database using the search term “Malaysia and tax”. The design of the study is bibliometric analysis. As of 23rd September 2020, a total of 88 documents were retrieved and analysed using Excel, Hazing’s Publish or Perish and VOSviewer software. Based on the standard bibliometric indicators, this paper reports the research papers and source types, years and language of publications, subject area, most active institutions, most active sources’ titles, keywords, authorship, abstract, title analysis and citation analysis. Findings revealed that there is an increase in growth rate of literature on studies related to taxation in the Malaysian context from 1977 to 2020 published in the Scopos database. The publications reached an all-time peak in 2016 to 2017 but significantly dropped in 2018 and 2019 based on the data retrieved from the Scopus database. The findings further show that Universiti Teknologi MARA is the most influential institution with 18.18% of the total documents retrieved, followed by Universiti Utara Malaysia with 9.1% respectively. Additional findings of the study show that Advance Science Letters is the highest source title with 14.71% of the published documents. The finding also indicates that Adhikari, Derashid and Zhang (2006) are the most influential authors with 187 citations as at 23rd September 2020. The research is limited to the literature's published in Scopus database, other database were not covered in this study. Malaysian policymakers should provide more research grants to tax practitioners and academicians to increase the level of publications in this field.